Respostas ao estresse osmótico e hipóxico em traíra, Hoplias malabaricus (Teleostei, Erythrinedae) aspectos fisiológicos e adaptativos - Sakuragui, Marise Margareth (Universidade Federal de São Carlos, 2006)
The stress level, via change in the plasma concentration of cortisol and the physiological and metabolic responses caused by osmotic shock and hypoxia and the effect of cortisol injection on theses responses, were studied in traíra, Hoplias malabaricus, injected and non-injected with cortisol exogenous (IC) and maintained in water similar to it natural environment (C- control) and in deionized water (AD) in normoxia (PO2 = 140 mmHg) and severe hypoxia (H, PO2 = 25-30 mmHg) during 48h. Animals injected with soy oil consisted the sham-operated group (TEST). Blood variables, pH, hematocrit (Hct) and hemoglobin concentration (Hb), osmolality, Na+, K+, and Cl- ion concentration, cortisol, glucose, lactate, ammonium and protein concentration were determined following 6, 12, 24, 36 and 48h in each experimental condition, after blood sample obtained via implanted catheter in the ventral vein. Twenty four and forty eight hours after the beginning of experiments, the gills of 5 animals from each group were removed for determination of Na+/K+-ATPase activity and chloride cell (CC) density using immunohistochemistry against Na+/K+-ATPase enzyme. Osmotic shock resulted in slow increasing of cortisol level in normoxia until 24h in group AD and fast increasing (6h) in fish exposed to hypoxia evidencing that the activation of hypothalamus hypophysis -interrenal axis depends on stressor agent. Cortisol injection (IC) in normoxia induced plasma glucose increasing in all experimental groups, with exception of AD group compared with controls that showed a tendency to increase only after 36-48h. During hypoxia, glucose increased in the DH+IC group only on the first 24h. Hydromineral unbalance, in normoxia, was observed with the increase of [Na+] and [K+] in all experimental groups and a decreasing of plasma [Cl-] only in the AD group in 6 and 24h, returning to values of control group after 36h, meanwhile, in hypoxia, the osmolality, [Cl-] and [Na+] decreased on the first 12, 6 and 12h, respectively, in non-injected groups. Transitory [K+] disturbance was observed in ADH (6h) and CH+IC (24 and 48h) groups. Changes in plasma glucose and lactate were observed in all injected groups in normoxia and hypoxia (with exception lactate concentration in CH+IC group), which evidences a possible effect of cortisol on these responses. In normoxia, the increasing of lactate, glucose and Na+ concentration in the injected groups may be related to exogenous cortisol and/or cholinergic activation instead of HHI activation axis. The changes of plasma glucose, lactate, pyruvate, ammonium and proteins suggested an increase of energy demand to homeostasis maintenance as a consequence of changes in cortisol. The significant increasing of pH may be due to metabolic alkalosis caused by a decreasing in plasma K+ and Cl- ions, which may stimulate the secretion of H+ ions to renal tubules in AD group in normoxia, while the increasing of pH in hypoxia may be explained by carbonic anhydrase activity in the erythrocytes with H+ production that combined with Hb+ or was changed with bicarbonate (HCO3 -/Cl-) in ADH. The reduction of pH, in hypoxia, in the ADH+IC group may be due to increase of lactate produced by cellular metabolism (acid metabolic). Hct showed a tendency to decrease, in normoxia, on the first 6h in C, TEST and AD groups and 12h in C+IC group, and to increase in the AD+IC group in 6 and 24h. In hypoxia, the Hct decreased on the first 6h in ADH+IC group and 12h in the CH, ADH e CH+ IC groups. Hb concentration did not change either in normoxia or hypoxia. Two chloride cell populations were identified in the gill filaments and lamellae of H. malabaricus; light-CC and dark-CC are restricted in the filaments an rarely in the lamellae. After osmotic and hypoxic stresses there were a density increase of CC of both types in the filament and lamella. Dark-CC density (mature and/or active) increased with the increase of cortisol levels and, consequently, the Na+/K+-ATPase activity followed these increasing in CC. The results of present study evidenced that the cortisol increasing above it basal level in H. malabaricus affect in the ionic equilibrium and energetic metabolism in fish kept in environment similar to it natural habitat. However, the effects of stress on the ionic equilibrium and metabolism may be reduced if cortisol level is above of the basal level of this species.
Keywords: Teleósteos; Hipóxia; Água deionizada; Cordisol; Intermediários metabólicos; Estresse; CIENCIAS BIOLOGICAS::ECOLOGIA